L-Carnitine Production Through Biosensor-Guided Construction of the Neurospora crassa Biosynthesis Pathway in Escherichia coli - Kugler, Pierre; Trumm, Marika; Frese, Marcel; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2021)
L-Carnitine is a bioactive compound derived from L-lysine and S-adenosyl-L-methionine, which is closely associated with the transport of long-chain fatty acids in the intermediary metabolism of eukaryotes and sought after in the pharmaceutical, food and feed industries. The L-carnitine biosynthesis pathway has not been observed in prokaryotes and the use of eukaryotic microorganisms as natural L-carnitine producers lacks economic viability due to complex cultivation and low titers. While biotransformation processes based on petrochemical achiral precursors have been described for bacterial hosts, fermentative de novo synthesis has not been established although it holds the potential for a sustainable and economical one-pot process using renewable feedstocks. This study describes the metabolic engineering of Escherichia coli for L-carnitine production. L-carnitine biosynthesis enzymes from the fungus Neurospora crassa that were functionally active in E. coli were identified and applied individually or in cascades to assemble and optimize a four-step L-carnitine biosynthesis pathway in this host. Pathway performance was monitored by a transcription factor-based L-carnitine biosensor. The engineered E. coli strain produced L-carnitine from supplemented L-Nε-trimethyllysine in a whole cell biotransformation, resulting in 15.9 µM carnitine found in the supernatant. Notably, this strain also produced 1.7 µM L-carnitine de novo from glycerol and ammonium as carbon and nitrogen source through endogenous Nε-trimethyllysine. This work provides a proof of concept for the de novo L-carnitine production in E. coli, which does not depend on petrochemical synthesis of achiral precursors but makes use of renewable feedstocks instead. To the best of our knowledge this is the first description of L-carnitine de novo synthesis using an engineered bacterium.